Hubungan Tingkat Aktivitas Fisik dan Performa Fisik dengan Kondisi Sarkopenia pada Penderita Obesitas Usia Lanjut di Komunitas - Annisa Budi Prayuni; Tirza Z Tamin; Wanarani Alwin; Dewi Friska (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
Introduction: Sarcopenic obesity (SO) is a condition in which sarcopenia and obesity occur simultaneously. This condition will lead to risk of higher morbidity, mortality, and reduced quality of life. This study aimed to examine the proportion of SO patients in community and investigate the association between physical activity level and physical performance with sarcopenia in elderly obese patient in community Methods: An analytic observation cross-sectional study with consecutive sampling. Inclusion criteria included subjects with age ≥ 60 years old, body mass index ≥ 25 Kg / m2, able to walk at least 10 meters, and has a good cognitive function. Subjects with pacemaker, have metal implants, history of cancer, acute cardiovascular and respiratory disorders, deformities, or pain in extremities and receive regular therapeutic exercise were excluded from this research. Measurement of physical activity level using Physical Activity Scale for Elderly (PASE) questionnaire and physical performance using 6meter walking speed test and timed up and go test (TUG). Sarcopenia is based on criteria from Asian Working Group of Sarcopenia 2019 with body composition assessment using Bioelectric Impedance Analysis (BIA) Results: There were 119 subjects in this study. Proportion of sarcopenia obesity in all subjects was 23,5% with 71,4% was female. The results showed that there was no significant association on physical activity level (p > 0,05) and a significant association on walking speed and TUG test (p < 0,05). Conclusion: This research concluded that there was a significant association between physical performance with sarcopenia in elderly obese patient in the community.